Impact des transitions urbaine et numérique sur la représentation des lieux - Dorothée Marchand; Émeline Bailly; Aimée Casal; Pierre Dias (Développement Durable et Territoires)
NUMCES research (Digital and creation of urban spaces) raises the question of the effect of urban and digital transition on the relationship between individuals and their living spaces. We carried out a survey with commented routes in an Île-de-France district, where an urban renewal project was in course. The results show that digital assessment and the transformation of the city vary according to the representation of the place, constructed by identity and urban values. This dual transition is accompanied by more uncertainties and worries than opportunities as to the consequences of this transitory situation.